Eternal Interns: Kathrin Röggla’s Literary Treatment of Gendered Capitalism - Florence Feiereisen (Studies in 20th & 21st Century Literature, 2011)
In today’s Germany, university graduates and first-time job seekers find themselves in a different position than did those of previous generations—for many, obtaining a secure, full-time job has become a dream of the past. To boost their résumés, many enter a loop of internships and other similarly precarious states of employment. This article examines the way in which author Kathrin Röggla treats these insecure economic times in her 2004 novel Wir schlafen nicht, with a focus on sex and gender in the New Economy. Are jobs gendered, and what are the resulting effects for both men and women? I discuss the continuum of business masculinity and femininity and argue that business masculinity (as performed by men or women) creates, and ultimately depends on, a feminization of the workforce. By personifying the New Economy and presenting her female characters as the losers of capitalism, Röggla unmasks grievances in contemporary Germany, revealing the entire economy’s process of feminization and its effects, which are borne more heavily by women than by men.
Keywords: university graduates; first-time job seekers; job seekers; résumés; internship; Kathrin Röggla; New Economy; Wir schlafen nicht; sex; gender; business; masculinity; femininity; feminization; performativity